Self-reported eating behaviors of military recruits are associated with body mass index at military accession and change during initial military training. (1st November 2019) - Fagnant, Heather S.; Armstrong, Nicholes J.; Lutz, Laura J.; Nakayama, Anna T.; Guerriere, Katelyn I.; Ruthazer, Robin; Cole, Renee E.; McClung, James P.; Gaffney-Stomberg, Erin; Karl, J. Philip
Abstract: Eating behaviors such as eating fast and ignoring internal satiety cues are associated with overweight/obesity, and may be influenced by environmental factors. This study examined changes in those behaviors, and associations between those behaviors and BMI, cardiometabolic biomarkers, and diet quality in military recruits before and during initial military training (IMT), an environment wherein access to food is restricted. Eating rate and reliance on internal satiety cues were self-reported, and BMI, body fat, cardiometabolic biomarkers, and diet quality were measured in 1389 Army, Air Force and Marine recruits (45% female, mean ± SEM BMI = 24.1 ± 0.1 kg/m 2 ) before and after IMT. Pre-IMT, habitually eating fast relative to slowly was associated with a 1.1 ± 0.3 kg/m 2 higher BMI (P < 0.001), but not with other outcomes; whereas, habitually eating until no food is left (i.e., ignoring internal satiety cues) was associated with lower diet quality (P < 0.001) and, in men, 1.6 ± 0.6% lower body fat (P = 0.03) relative to those that habitually stopped eating before feeling full. More recruits reported eating fast (82% vs 39%) and a reduced reliance on internal satiety cues (55% vs 16%) during IMT relative to pre-IMT (P < 0.001). Findings suggest that eating behaviors correlate with body composition and/or diet quality in young, predominantly normal-weight recruits entering the military, and that IMT is associated with potentially unfavorable changes in these eating behaviors.